The Analysis of Constitutional Court Decision Number 114/PUU-XX/2022 Regarding the Judicial Review of the Proportional System in General Elections - Dwi Altin Fajrunnafi'; Hananto Widodo (NOVUM : JURNAL HUKUM, 2026)
This study analyzes Constitutional Court Decision Number 114/PUU-XX/2022 concerning the judicial review of Law Number 7 of 2017 on the general election proportional system in Indonesia. The issue arises from a perceived constitutional inconsistency between the open-list proportional system adopted in the law and the 1945 Constitution, particularly in how it diminishes the institutional role of political parties in elections. The petitioners argued that the current system undermines party functions, promotes individualism, and facilitates money politics. The objective of this study is to critically assess the Constitutional Court's decision, which rejected the petition on the grounds of open legal policy and lack of legal reasoning. It also aims to evaluate whether the Court should have adopted a judicial activism approach in reviewing the proportional electoral system. Using a normative juridical method, the research relies on primary and secondary legal sources, including statutory regulations and constitutional principles, to analyze the legal reasoning behind the Court's decision and its broader implications. The findings suggest that although the Court emphasized legislative discretion, it missed an opportunity to assert its role as a negative legislator to address the legal and moral inconsistencies of the open-list system. The study concludes that a limited open proportional system may serve as a more balanced alternative—preserving voter choice while reinforcing political party roles. Strengthening party cadre systems is also recommended to ensure democratic integrity and effective political representation.